2016
DOI: 10.3390/ijerph13050502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Substance Use and Misuse among Kosovar Adolescents; Cross Sectional Study of Scholastic, Familial-, and Sports-Related Factors of Influence

Abstract: Adolescence is considered to be the most important period for the prevention of substance use and misuse (SUM). The aim of this study was to investigate the problem of SUM and to establish potentially important factors associated with SUM in Kosovar adolescents. Multi-stage simple random sampling was used to select participants. At the end of their high school education, 980 adolescents (623 females) ages 17 to 19 years old were enrolled in the study. The prevalence of smoking, alcohol consumption (measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 38 publications
(70 reference statements)
9
44
0
1
Order By: Relevance
“…It is likely that the cultural heritage of this territory (i.e., a significant portion of former Yugoslavia was part of the Ottoman Empire for more than four centuries) has played a role in smoking being looked upon as a socially accepted behavior, and availability of tobacco products has played important role in the relatively stable adolescent smoking figures. The role of these factors has been supported in studies examining other countries within this region [3,4,5]. Also, it has been approximated that more than one-fourth of the tobacco market in Croatia originates from the black market [6], which has significantly diminished the potential effect of higher prices of tobacco because of the taxing (increase of approximately 17% during the last five years) on smoking prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the cultural heritage of this territory (i.e., a significant portion of former Yugoslavia was part of the Ottoman Empire for more than four centuries) has played a role in smoking being looked upon as a socially accepted behavior, and availability of tobacco products has played important role in the relatively stable adolescent smoking figures. The role of these factors has been supported in studies examining other countries within this region [3,4,5]. Also, it has been approximated that more than one-fourth of the tobacco market in Croatia originates from the black market [6], which has significantly diminished the potential effect of higher prices of tobacco because of the taxing (increase of approximately 17% during the last five years) on smoking prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Research on gender differences in the relationship between sport and smoking, alcohol and drug abuse is small and inconsistent; for instance, while Stafforter, Storger and Larsen (2005) found that membership in organized sport teams, increase the risk of alcohol abuse in male and female adolescents (28), more recent research, introduce competitive sport as a risk factor for alcohol abuse among females and a factor in preventing smoking among males (29). Despite the research being accomplished so far, there is no clear answer to the question that "Does sport help preventing and reducing the abuse of drug, alcohol and smoking in young people as it believed in public ".…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, when sport participation was analysed more specifically, there were some conflicting findings with the association between sports and cigarette smoking. [26][27][28] For example, in a recent study, authors found that adolescents who had stopped participating in a sport were at high risk of misusing substances, while lower competitive achievement in sports was found to be associated with a higher likelihood of cigarette smoking. 3 5 27 Again, owing to the cross-sectional study design, the causality is not clear.…”
Section: Introductionmentioning
confidence: 99%